2018
DOI: 10.1021/acsabm.8b00491
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-ZnO Scaffolds for Wound Healing Applications: Role of Dendrimer Functionalization and Nanoparticle Morphology

Abstract: Functionalized nanoparticle cross-linked collagen scaffolds offer improved properties to biomaterials and regenerated tissues, as influence of nanoparticle shape on collagen scaffold has received little attention. The present study evaluates the role of ZnO nanoparticle shape (sphere, rod, hexagonal, needle, flower, star, circular disk, doughnut, and cube) on collagen self-assembly. The nanoparticle was prepared by using coprecipitation method and subsequently functionalized with triethoxysilane poly­(amidoami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Inspire of these reports, our group have studied an effect of various morphology of TES-PAMAM-G 1 dendrimer functionalized ZnO nanoparticle cross-linked collagen scaffold in skin regenerative application. The result obtained in that study indicated the sphere shape of ZnO nanoparticle exhibited a better-wound healing process than other shapes [27]. The use of PAMAM based dendrimer in that study is due to their well-de ned nanostructured macromolecules with relatively low toxicity and large number of surface functional groups leading to higher cross-linking density with collagen through EDC-NHS treatment [28][29].This cross-linking method is highly e cient, nontoxic (EDC-NHS used to activate the carboxylic groups of collagen and do not take part in cross-linking reaction) and the resultant by product can be easily removed by washing process [30].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Inspire of these reports, our group have studied an effect of various morphology of TES-PAMAM-G 1 dendrimer functionalized ZnO nanoparticle cross-linked collagen scaffold in skin regenerative application. The result obtained in that study indicated the sphere shape of ZnO nanoparticle exhibited a better-wound healing process than other shapes [27]. The use of PAMAM based dendrimer in that study is due to their well-de ned nanostructured macromolecules with relatively low toxicity and large number of surface functional groups leading to higher cross-linking density with collagen through EDC-NHS treatment [28][29].This cross-linking method is highly e cient, nontoxic (EDC-NHS used to activate the carboxylic groups of collagen and do not take part in cross-linking reaction) and the resultant by product can be easily removed by washing process [30].…”
Section: Introductionmentioning
confidence: 79%
“…Triethoxy silane poly (amido amine) dendrimer (TES-PAMAM-G 3 or G 3 ) was synthesized by using our previously reported procedure (Fig. S1, Supplementary le) [27].…”
Section: Synthesis Of Tes-pamam -G 3 Dendrimer -Divergent Methodsmentioning
confidence: 99%
“…In addition, the scaffold allows the transfer and removal of the nutrients of toxic metabolites/by-products from in and out of the tissues. The scaffold’s physicochemical properties, mechanical strength, and biocompatibility depend on the three-dimensional architecture and chemical composition [ 11 , 12 , 15 ]. Hence, the fabricated scaffold should possess the following properties for tissue engineering application (1) high porosity with interconnected pore structure, (2) larger surface area, (3) suitable mechanical strength, (4) better biocompatibility, and (5) controlled biodegradation for sufficient cell-scaffold interaction [ 18 , 19 , 20 ].…”
Section: Cds Mediated Scaffold For Tissue Engineering Applicationmentioning
confidence: 99%
“…Over the years, various tissue engineering constructs such as film, sponge, membrane, fiber, hydrogel, and 3D ink scaffold have been developed by many researchers to achieve success in tissue regeneration [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The biocompatible scaffolds closely mimic the three-dimensional (3D) architecture of native tissue, aiding cellular events such as attachment, proliferation, and differentiation [ 15 , 16 ]. Mostly, scaffolds are fabricated using natural and synthetic polymers through phase separation, self-assembly, gas foaming, and particulate leaching, emulsification, and electrospinning method, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas a few studies have demonstrated the ability of (nano)rods to improve the mechanical stability of collagen hydrogels, none of them used magnetic particles to control the material orientation [38,39]. In addition to the aforementioned advantages of silica-based particles in terms of biocompatibility and drug delivery, their combination with collagen has already been demonstrated useful for bone and skin repair [40,41], which may benefit from controlled fiber orientation [37], and opening perpective in other tissue engineering applications such as nerve regeneration [36].…”
Section: Introductionmentioning
confidence: 99%